Participant Recruitment Challenges in Researching Peer Groups and Migration Retrospectively - Paula Pustułka; Natalia Juchniewicz; Izabela Grabowska (Przeglad Socjologii Jakosciowej, 2017)
This paper discusses the challenges of researching peer groups through a multi-focal, temporal lens in a retrospective manner. Embedded in a broader “Peer Groups & Migration” Qualitative Longitudinal Study (QLS), the article focuses on recruiting young respondents (aged 19-34 at present) who originally come from one of the three medium-sized towns in Polish localities and are either migrants or stayers connected to mobile individuals. The respondents are tracked retrospectively and asked to discuss their adolescence, as well encouraged to provide contacts to their youth Peer Group members. Based on fieldwork experiences and field access challenges, four models of recruiting migrants’ high school peer groups are presented. Furthermore, variants and rationales of non-recruitment are also provided. Focusing on the process of establishing a long-term and large-scale peer panel in the QLS, the paper contributes detailed know-how and strategies around participant recruitment.